The Significance Of Psalm Singing In Calvin's Liturgy Of The Lord's Supper And Its Relevance Today - Yudha Thianto (STT Reformed Injili Internasional, 2021)
In this article, the author argues of the significance of Psalm singing in Calvin's Liturgy of the Lord's Supper. Metrical psalm singing is one of Calvin's contributions towards the changes in reformation worship. Furthermore, his emphasis on its use in the Liturgy of the Lord's Supper is an important retrieval from the wider diversity in many contemporary church worship. Throughout the article, the author endorses a creative use of psalm singing in the church. Such practice must not be forgotten that has been formative to the reformation in the past.